The necessity of a multidisciplinary approach in the treatment of eating disorders - Djukic, Sladjana; Olajdžija, Tanja (Education and Research in Health Sciences, 2026)
Eating disorders represent complex psychosomatic conditions that require a comprehensive and strictly individualized approach to treatment. The aim of this paper is to present the specific characteristics of the treatment of anorexia nervosa, bulimia nervosa and binge eating disorder, with particular emphasis on nutritional, pharmacological, and psychosocial approaches, focusing on family involvement and social support. The paper examines key principles of treatment, including respect for individual patient characteristics, the influence of family and social environment, and the importance of early intervention. Treatment methods include psychotherapy (individual, behavioral and family therapy), a tailored nutritional plan, monitoring of body weight and overall health status, as well as multidisciplinary coordination among healthcare professionals. The results indicate that a combined approach integrating psychological support and nutritional intervention contributes to gradual weight restoration, reduction of anxiety, and reintegration of patients into everyday life. Special attention is given to stress management, relapse prevention and adaptation to new life routines. It is concluded that a holistic, tactful and humane approach is essential for successful treatment, with continuous support from family and a multidisciplinary team, taking into account both the physical and psychological aspects of the disorder.